Histopathological findings of diseased ascending aortae with clinicopathological correlation - A single-centre study of 160 cases - Stejskal, Vaclav; Karalko, Mikita; Krbal, Lukas (Pathology, research and practice, 2023)
The most common reason for ascending aorta resection is an aneurysm or dissection. Aortic dissection is a life-threatening condition in which an aneurysm is a crucial risk factor. The essential criteria for aneurysm resection include the diameter, genetic predisposition, and aortic valve disease. This study aimed to compare the histological findings in aneurysms and dissections and correlate them with clinical parameters to determine whether histopathological findings correspond with the current clinical approach. A total of 160 ascending aorta surgical specimens, separate or with an aortic valve, were collected and divided into four groups: aneurysm-tricuspid (n = 40; median 67 y), aneurysm-malformed (n = 68; median 50 y), dissection-tricuspid (n = 48; median 65.5 y), and dissection-malformed (n = 4; median 52.5 y). Male preponderance was observed in all groups; the youngest patients were in the aneurysm-malformed group. None of the specimens showed normal aortic histology. The most common finding in the aortic samples was medial degeneration, which was the most severe and most common in dissection. The mildest findings were found in the aneurysm-malformed group. Atherosclerosis was predominant and most severe in the aneurysm-tricuspid group, while only mild in both dissection groups, suggesting its protective effect against this complication. Chronic aortitis was the least common pathology, found only in the aneurysm-tricuspid group. The aortic valve was resected and examined simultaneously with the ascending aorta in 76 cases, most commonly in the aneurysm-malformed group (n = 53). Myxoid degeneration was the major finding in the tricuspid aortic valves, with calcifications in the malformed. Comparing the histopathological results with the clinical aspects, aneurysms with a malformed aortic valve seem to be managed appropriately, with the findings not reaching the severity as in patients with a tricuspid valve. In contrast, in patients with a tricuspid valve, there were more dissections than aneurysms, with a significant subset of aneurysms showing histological findings almost identical to those of dissections. Supported by histological findings, patients with a diseased ascending aorta and tricuspid aortic valve represent an underdiagnosed risk group that would benefit from earlier diagnosis and intervention to prevent dissection. There is a need to find a marker for dissection risk other than the aortic diameter.
Keywords: aorta; Humans; rizikové faktory; Ascending aorta; Aortic Dissection; lidé; Aortic valve; Male; Atherosclerosis; Aortic Valve; Genetic Predisposition to Disease; disekce aorty; genetická predispozice k nemoci; Aortic aneurysm; Medial degeneration; mužské pohlaví; Aorta; aortální chlopeň; Aortic dissection; Risk Factors